Methane-filled hollow fiber: a cost-effective pathway to compress high repetition rate ytterbium femtosecond lasers using self-phase modulation - Mayank Kumar; Tristan Guay; Heide Ibrahim; François Légaré (Applied Physics Express)
Hollow-core fiber (HCF) based temporal pulse compression is widely used to generate few-cycle pulses. Here, we demonstrate the strength of methane (CH _4 ) as a nonlinear medium for HCF-based pulse compressors to achieve high average power few-cycle pulses of sub-16 fs duration with >70% transmission and up to 250 kHz repetition rate in a compact setup and present it as a cost-effective alternative to highly expensive and scarcely available noble gases.